New Baitouweng decoction combined with fecal microbiota transplantation alleviates DSS-induced colitis in rats by regulating gut microbiota metabolic homeostasis and the STAT3/NF-κB signaling pathway - Xin Gu; Zhiwei Miao; Yantian Wang; Yue Yang; Tongtong Yang; Yi Xu (BMC, 2022)
Abstract Aim of the study We aimed to elucidate the synergistic effect and potential mechanism of New Baitouweng Decoction (NBD) combined with fecal microbiota transplantation (FMT) in rats with DSS-induced ulcerative colitis (UC). Materials and methods Colitis was induced by 5% (w/v) dextran sulfate sodium (DSS) in drinking water for 7 days. NBD or NBD combined with FMT were administered to the colitis rats. Body weight and disease activity index were measured, and the colon histological change was imaged to further examine the efficacy of NBD and FMT. The specific effects of NBD on STAT3/NF-κB signaling pathway and gut microbiota in rats with UC were also investigated. Results The efficacy of NBD in combination with FMT was demonstrated by the lower disease activity index scores; increased tight junction proteins expression; and a lower expression of macrophage marker (F4/80) in colon tissues. NBD combined with FMT elevated the concentrations of short-chain fatty acids and inhibited activation of the JAK2/STAT3/NF-κB related proteins. Furthermore, 16SrDNA sequencing indicated that the gut microbiota in rats with UC was perturbed, in contrast to that in healthy rats. After treatment with NBD and FMT, the diversity and abundance of intestinal flora showed clear improvements. Spearman correlation analysis indicated a strong correlation between specific microbiota and fecal concentrations of acetate, propionate and butyrate. Conclusions The protective mechanism of NBD combined with FMT may be linked to regulation NF-κB/STAT3 and restoration of the intestinal flora.